Corneal thickness and curvature of one sample of young myopic population in Malaysia - Bariah Mohd-Ali; Ho, Oi Ching; Nor Azizah Abd Latif (Penerbit UKM, 2009)
The purpose of this study is to determine the standard value of corneal thickness (CCT) and its relationship with the degree of myopia amongst one sample of myopic students in Malaysia. Eighty-four myopic subjects (168 eyes) were examined in this study. Ocular examination included subjective refraction, keratometry (Shin-Nippon, Japan) and optical pachometry (Sonogage INC). Corneal thickness was measured at five different locations i.e. central, superior, inferior, nasal and temporal of the cornea. However, only association of CCT with myopia is reported in this article. Mean age of subjects was 21.42 ± 1.47 years old (20.34 ± 1.15; 22.46 ± 0.88). Mean refractive error in spherical equivalent for the whole sample was –3.50 ± 2.10 DS. Mean corneal curvature for the all subjects was 7.74 ± 0.52 mm and mean value of CCT was 594.62 ± 66.51 mm. Significant differences (p < 0.05) were found between mean CCT of low myopes (-4.00DS and below) and higher ones (-4.25DS and above), but not with mean of keratometer readings. Poor correlations were obtained between refractive error and CCT (r = 0.125, p > 0.05) and between refractive error and corneal curvature (r = 0.24, p > 0.05). It was concluded from this study that high myopic subjects has significantly thinner CCT than lower ones. Measurement of CCT should be considered when undertaking procedures such as LASIK and orthokeratology.